The governance of climate change adaptation in developing countries : the case of national disaster management in Bangladesh and Pakistan in comparative perspective - Peissker, Tina (Anchor Academic Pub., 2013)
Hauptbeschreibung The prospect of the adverse effects that global climate change will have on human societies, opened up a discourse about the way adaptation should be managed. In order to finance adaptation measures in the most severe affected countries, the parties of the Kyoto Protocol established the Adaptation Fund in 2007. In view of the limited resources that are available for adaptation, scales for the prioritization of countries that are based on their suspected vulnerability, have been developed in literature. But so far, indicators of vulnerability reflect only the genera.